Why should we ask binge drinkers if they smoke cannabis? Additive effect of alcohol and cannabis use on college students' neuropsychological performance. (December 2021) - Deniel, Simon; Mauduy, Maxime; Cheam-Bernière, Caroline; Mauny, Nicolas; Montcharmont, Charlotte; Cabé, Nicolas; Bazire, Anaëlle; Mange, Jessica; Le Berre, Anne-Pascale; Jacquet, Denis; Bagneux, Virginie; Leconte, Pascale; et al.
Highlights: This study focused on combined binge drinking and cannabis use in college students. Cannabis use and binge drinking had an additive effect on cognition. This consumption pattern contributed to memory and executive impairments. Binge drinkers had a heterogeneous cognitive profile regardless of cannabis use. Cannabis use should be assessed in binge drinkers to adapt prevention strategies. Abstract: Introduction: Binge drinking (BD) and cannabis use are prevalent in European adolescents and students. BD has been shown to have a negative impact on neuropsychological functioning, but little is known about the additive effect when it is combined with cannabis consumption. We therefore investigated the neuropsychological profiles of students who engage in combined BD and cannabis use, in order to explore the potentially harmful additive effects of cannabis use and BD on cognition. Material and methods: A sample of college students ( N  = 298) completed questionnaires on alcohol and cannabis use, and were screened for neuropsychological impairments using the Brief Evaluation of Alcohol-Related Neuropsychological Impairments (BEARNI). First, after dividing students into three groups according to their alcohol and cannabis use (i.e., light drinkers, binge drinkers, and binge drinkers consuming cannabis), we ran a linear mixed model based on the BEARNI z scores to test the performances of the three groups. Information yielded by the mixed model was supplemented by individual analyses. Second, to explore the heterogeneity of binge drinkers' profiles, we ran a cluster analysis to characterize the alcohol users at higher risk of more severe neuropsychological impairment. Results: Overall, poorer neuropsychological performances were observed among binge drinkers compared with light drinkers, whether they used cannabis or not. However, flexibility, episodic memory and working memory were particularly affected among binge drinkers who used cannabis. Conclusions: Results emphasize the importance of asking binge drinkers if they smoke cannabis, in order to adapt care and prevention strategies to their consumption and neuropsychological profile.